KAIDAH-KAIDAH TAFSIR YANG BERHUBUNGAN DENGAN AMR (PERINTAH) DAN NAHY (LARANGAN) DI DALAM AL-QUR’AN - Dr. Zainuddin Hamkah (Ash-Shahabah : Jurnal Pendidikan dan Studi Islam, 2017)
The Qur'an as a guide of life for Muslims and Muslims in which the contents consist of three components, the first contains aqidah (Tawheed), the second contains Amr (command) and nahy (ban) and the third contains history. Aqeedah (Tawheed) as an order to bring God out of equality with His creatures both in terms of substance, nature, asthma and affial. Amr is a form of command in the Qur'an that means God's demand to a believer who is baligh to execute it. And sighat amr in the Qur'an varies for example using faradla sentence or kutiba, or mention that the act is forbidden by God. In the Qur'an, Uslub (style of language) in banning also vary, such as using Mudlari fi'il, accompanied by La nahiyah, using naha, haram, unlawful or calling that deed is a sin, or that act Is bad and evil